Visible-light photocatalytic activation of N-chlorosuccinimide by organic dyes for the chlorination of arenes and heteroarenes. Issue 36 (6th September 2019) - Rogers, David A.; Gallegos, Jillian M.; Hopkins, Megan D.; Lignieres, Austin A.; Pitzel, Amy K.; Lamar, Angus A.
Abstract: A variety of arenes and heteroarenes are chlorinated in moderate to excellent yields using N-chlorosuccinimide (NCS) under visible-light activated conditions. A screening of known organic dye photocatalysts resulted in the identification of methylene green as the most efficient catalyst to use with NCS. According to mechanistic studies described within, the reaction is speculated to proceed via a single electron oxidation of NCS utilizing methylene green under visible-light photoredox pathway. The photo-oxidation of NCS amplifies the electrophilicity of the chlorine atom of the NCS, thus leading to enhanced reactivity as a chlorinating reagent with aromatic substrates. Graphical abstract: Image 1 Highlights: The first example of non-metal photo-oxidative activation of N-chlorosuccinimide by a visible-light photoredox catalyst. Utilization of methylene green, an inexpensive visible-light photoredox catalyst in the thiazine family of organic dyes. Good to excellent yields of chlorinated (hetero)arenes using mild reaction conditions (ambient temperature, open to air). Wide range of functional group tolerance – a feature important for fine chemical chlorination of complex molecules.